Phase 2 randomised study of bulevirtide as monotherapy or combined with Peg-IFNα-2a as treatment for chronic hepatitis delta - Lampertico, Pietro; Bogomolov, Pavel O.; Chulanov, Vladimir; Stepanova, Tatiana; Morozov, Viacheslav; Allweiss, Lena; Dandri, Maura; Burhenne, Jürgen; Blank, Antje; Ciesek, Sandra; Elsner, Carina; Dittmer, Ulf; et al. (Liver international, 2025)
Background and Aim Bulevirtide (BLV) leads to beneficial virologic and biochemical responses when given alone to treat hepatitis delta virus (HDV) infection, which causes the most severe form of chronic viral hepatitis. We evaluated 48 weeks of BLV monotherapy, BLV + tenofovir disoproxil fumarate (TDF) and BLV + pegylated interferon alfa-2a (Peg-IFNα-2a), with 24-week follow-up. Methods Ninety patients were enrolled into six arms of 15 each (A-F); 60 patients were included in the main randomisation (arms A-D), and 30 patients (arms E-F) were randomised to the extension phase: (A) Peg-IFNα-2a 180 μg once weekly (QW); (B) BLV 2 mg once daily (QD) + Peg-IFNα-2a 180 μg QW; (C) BLV 5 mg QD + Peg-IFNα-2a 180 μg QW; (D) BLV 2 mg QD; (E) BLV 10 mg QD + Peg-IFNα-2a 180 μg QW and (F) BLV 10 mg (5 mg twice daily) + TDF QD. The primary endpoint was undetectable HDV RNA at week (W)72. Results At W72, 53%, 27%, 7%, 7% and 33% of patients achieved undetectable HDV RNA in arms B, C, D, E and F, respectively, versus 0% in arm A. More arm B versus A patients had a > 1 log10 IU/mL decline in or loss of hepatitis B surface antigen (HBsAg) at W72 (p = 0.017), including four patients with loss of HBsAg. Bile acid elevations were dose-dependent and reversible following the completion of BLV treatment. Conclusions BLV combined with Peg-IFNα-2a was well tolerated and resulted in high rates of HDV RNA undetectability off-treatment.